Defense-in-depth vs. Critical Component Defense for Industrial Control Systems - Fielder,A; Li,T; Hankin,C (BCS Learning & Development Ltd., 2016)
Originally designed as self-contained and isolated networks, Industrial Control Systems (ICS) have evolved tobecome increasingly interconnected with IT systems and other wider networks and services, which enablescyber attacks to sabotage the normal operation of ICS. This paper proposes a simulation of attackers anddefenders, who have limited resources that must be applied to either advancing the technology they haveavailable to them or attempting to attack (defend) the system. The objective is to identify the appropriatedeployment of specific defensive strategy, such as Defense-in-depth and Critical Component Defense.The problem is represented as a strategic competitive optimisation problem, which is solved using a coevolutionaryParticle Swarm Optimisation problem. Through the development of optimal defense strategies,it is possible to identify when each specific defensive strategies is most appropriate; where the optimaldefensive strategy depends on the kind of attacker the system is expecting and the structure of the network.